Adoption of soil and water conservation technologies in an upland community in Impasug-ong, Bukidnon, Philippines - Pulhin, Juan M. (Journal of Environmental Science and Management, 2002)
As enacted through Republic Act 8435, better known as the Agriculture and Fisheries Modernization Act (AFMA) of 1997, the modernization of the agriculture and fisheries sectors promotes the use of approriate technologies that would protect the environment, reduce production cost, and increase the global competitiveness of farmers. Hence, the adoption of soil and water conversation and other farming technologies is critical to the success of AFMA. Previous studies suggest that the socioeconomic and related factors that influenced the farmers' adoption of soil and water conservation technologies in Barangay La Fortuna, Impasugong, Bukidnon, Philippines.